Exploiting flexibility of end-users at DSO-TSO levels acting in dynamic coalitions - Lezama, Fernando (2021)
In this paper, we propose and analyze a coalitional game in which end-users with different characteristics and preferences can cooperate to offer their flexibility to upper-level entities such as the DSO and TSO. We formulate the problem as a cooperative game in which users need to decide the percentage of flexibility they want to offer to DSO and TSO, while searching for the coalition structures that maximize their utilities. Finding the optimal coalition structure that maximizes the sum of payoffs (i.e., social welfare) is a complex combinatorial problem that cannot be efficiently solved for large instances. Therefore, we evoke the use of computational intelligence algorithms to find near-optimal solutions that can provide higher pay-offs in acceptable times than, for example, the grand coalition and independent coalitions.